2002
DOI: 10.1053/gast.2002.31001
|View full text |Cite
|
Sign up to set email alerts
|

Steatosis and liver cancer in transgenic mice expressing the structural and nonstructural proteins of hepatitis C virus

Abstract: Constitutive expression of viral proteins leads to common pathologic features of hepatitis C in the absence of specific anti-viral immune responses. Expression of the structural proteins enhances a low background of steatosis in C57BL/6 mice, while additional low level expression of nonstructural proteins increases the risk of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
382
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 429 publications
(399 citation statements)
references
References 51 publications
(68 reference statements)
14
382
1
2
Order By: Relevance
“…It has been demonstrated that expression of HCV core protein alone is sufficient for the induction of hepatic steatosis and hepatocellular carcinoma in transgenic mice (24,34,35). Furthermore, we demonstrated that nuclear localization and degradation of HCV core protein is regulated by PA28␥-dependent proteolysis (33).…”
Section: Discussionmentioning
confidence: 58%
“…It has been demonstrated that expression of HCV core protein alone is sufficient for the induction of hepatic steatosis and hepatocellular carcinoma in transgenic mice (24,34,35). Furthermore, we demonstrated that nuclear localization and degradation of HCV core protein is regulated by PA28␥-dependent proteolysis (33).…”
Section: Discussionmentioning
confidence: 58%
“…These transgenic mice have exhibited two phenotypes: those with and those without hepatic tumors. The tumor phenotype has been reported to occur in transgenic mice for core, 6 the entire region, 9 or coreϩE1ϩE2. 9 However, in different investigations mice transgenic for core, 10 E2, 10 E1ϩE2, 3 and coreϩE1ϩE2, 2 did not exhibit the tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…2 We used the albumin promoter as did Lerat et al 9 The transgenic mice developed by Kawamura et al demonstrated high core expression, 2 whereas those by Lerat et al showed much lower core protein expression, suggesting that levels of core protein expression alone do not explain the HCC phenotype, and that the FVB background may have a protective role in hepatocarcinogenesis. Indeed, saline-treated control animals expressing the core and core-E1-E2 construction on the FVBϫC57Bl/6 background both failed to develop HCC, unless they were exposed to a chemical carcinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly more nuclei were stained positively for Cre at days 5 and 7 post-induction, and it later disappeared from the nuclei via an as-yet-unidentified mechanism, at days 14 and 21 post-induction. In a previous study, constitutive version of the SL24 transgene resulted in cytoplasmic staining for core and E2 predominantly in pericentral hepatocytes (Lerat et al, 2002). Given the limitations associated commonly with the current constitutive and inducible tg animals, for example, immunotolerance due to premature HCV expression and inflammatory responses against adenoviral vector (Lerat et al, 2002;Sun et al, 2005;Wakita et al, 1998), this novel HCV mouse model offers several obvious advantages, including controlling temporally HCV expression without viral vector-or hydrodynamics-related complications in animals.…”
Section: Tamoxifen Induction Of Hcv Structural Proteins In Tg Micementioning
confidence: 94%
“…Copy numbers of the recombined transgene in the liver were assessed by real-time quantitative PCR on a LightCycler using a QuantiTect SYBR Green PCR kit (Qiagen, Inc., Valencia, CA). A standard curve was generated for the recombined transgene with pALB.HCV-S (Lerat et al, 2002), which was quantified with a Quant-iT PicoGreen dsDNA kit (Qiagen). The amplification reactions were carried out with 5-μl sample aliquots in a 20-μl final volume.…”
Section: Determination Of Cre-mediated Dna Recombinationmentioning
confidence: 99%